Balaenoptera acutorostrata Lacépède 1804 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Balaenoptera acutorostrata Lacépède 1804 Balaenoptera acutorostrata Lacépède 1804, Hist. Nat. Cetacees: 134. Type Locality: France, "pris aux environs de la rade de Cherbourg", Mancha. Vernacular Names: Common Minke Whale. Synonyms: Balaenoptera davidsoni Cope 1872; Balaenoptera minima (Rapp 1837); Balaenoptera rostrata (Fabricius 1780). Distribution: Worldwide: arctic to tropical waters. Conservation: CITES – Appendix I (except the population of West Greenland, which is Appendix II); IUCN – Lower Risk (nt). Discussion: Reviewed by Stewart and Leatherwood (1985). Two forms have been described from SW Pacific waters (Arnold et al., 1987). May represent two or three species (Wada and Numachi, 1991). Deméré (1986) reassigned Eschrichtius davidsonii (Cope 1872) to Balaenoptera , making B. davidson i Scammon 1872 a junior synonym and erecting Balaenoptera acutorostrata scammoni Deméré, 1986 as a substitute. Rice (1998:70) recognized B. a. scammoni (Scammon’s Minke Whale) and another un-named subspecies in the southern hemisphere ( B. a . subsp.; Dwarf Minke Whale). We recognize that there are probably others, like the population in the Sea of Japan. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 724, DOI: 10.5281/zenodo.7316519